PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DOSEN JURUSAN BIMBINGAN DAN KONSELING DI FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MEDAN - Nani Barorah Nasution; Nasrun Nasrun; Dody Feliks Pandimun Ambarita; Husna Parluhutan Tambunan (Universitas Negeri Medan, 2020)
Abstract: The Influence ff Organizational Culture And Work Satisfaction On Organizational Commitments Of Lecturers And Counseling Department At The Faculty Of Education, Medan State University. The purpose of this study was to determine the effect of organizational culture and job satisfaction on organizational commitment of the guidance and counseling lecturers at the Faculty of Education, State University of Medan. This research is a quantitative research with a path analysis approach that starts from April to December 2020. The population and sample are all lecturers in the department of guidance and counseling at the Faculty of Education, State University of Medan, both PNS and PHL, totaling 23 lecturers. The results showed that there was a direct influence of organizational culture on job satisfaction, a direct influence of organizational culture on organizational commitment and a direct effect of job satisfaction on organizational commitment. Based on these findings, it can be concluded that organizational commitment is influenced by organizational culture and job satisfaction. Therefore, increasing organizational commitment can be done by increasing organizational culture and job satisfaction. Keywords: Organizational Culture, Job Satisfaction, Organizational Commitment. Abstrak: Pengaruh Budaya Organisasi Dan Kepuasan Kerja Terhadap Komitmen Organisasi Dosen Jurusan Bimbingan Dan Konseling Di Fakultas Ilmu Pendidikan Universitas Negeri Medan. Tujuan penelitian ini adalah untuk mengetahui pengaruh budaya organisasi dan kepuasan kerja terhadap komitmen organisasi dosen jurusan bimbingan dan konseling di Fakultas Ilmu Pendidikan Universitas Negeri Medan. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan analisis jalur yang dimulai pada bulan April sampai dengan Desember 2020. Populasi dan sampel adalah seluruh dosen jurusan bimbingan dan konseling di Fakultas Ilmu Pendidikan Universitas Negeri Medan baik PNS maupun PHL sebanyak 23 dosen. Hasil penelitian menunjukkan adanya pengaruh langsung budaya organisasi terhadap kepuasan kerja, pengaruh langsung budaya organisasi terhadap komitmen organisasi dan pengaruh langsung kepuasan kerja terhadap komitmen organisasi. Berdasarkan temuan tersebut dapat disimpulkan bahwa komitmen organisasi dipengaruhi oleh budaya organisasi dan kepuasan kerja. Kata Kunci: Budaya Organisasi, Kepuasan Kerja, Komitmen Organisasi.